The biology of polar regions - Thomas, David N. (David Neville), 1962-; Fogg, G. E. (Gordon Elliott), 1919- (Oxford : Oxford University Press, 2008)
There is an increased awareness of the importance of polar regions, and their vulnerability to anthropogenic derived change. This book offers an introduction to polar ecology. The emphasis is on the organisms that dominate these environments although pollution, conservation and experimental aspects are also considered.
Rev. ed. of: The biology of polar habitats / G.E. Fogg. 1998.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Ecology -- Polar regions; Natural history -- Polar regions